(untitled) (Contemporary Mathematics, 2024)
In this paper, we presents strong and ∆-convergence results within the framework of CAT(0) space for pseudomonotone mappings. Additionally, we approximate the solution for variational inequality problems in the context of CAT(0) space for such mappings. Lastly, we provide a numerical example to highlight our main result.